2012
DOI: 10.1210/en.2012-1016
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Therapeutic Approach to Treating Obesity through Modulation of TGFβ Signaling

Abstract: Obesity results from disproportionately high energy intake relative to energy expenditure. Many therapeutic strategies have focused on the intake side of the equation, including pharmaceutical targeting of appetite and digestion. An alternative approach is to increase energy expenditure through physical activity or adaptive thermogenesis. A pharmacological way to increase muscle mass and hence exercise capacity is through inhibition of the activin receptor type IIB (ActRIIB). Muscle mass and strength is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 46 publications
4
88
0
Order By: Relevance
“…Although diverse aspects of metabolism are subjected to circadian regulation (Bass and Takahashi, 2010;Green et al, 2008), whether the adipocyteintrinsic timekeeping mechanism participates in brown fat cell development is not known. Our study demonstrates that the essential transcription activator of the molecular clock, Bmal1, exerts direct temporal control of the TGF-b pathway, a key inhibitory signal of brown fat formation (Fournier et al, 2012;Koncarevic et al, 2012;Yadav et al, 2011). Together with reciprocally altered BMP activity, these developmental signaling mechanisms driven by Bmal1 modulate brown adipogenesis and consequently affect adaptive thermogenesis in vivo.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Although diverse aspects of metabolism are subjected to circadian regulation (Bass and Takahashi, 2010;Green et al, 2008), whether the adipocyteintrinsic timekeeping mechanism participates in brown fat cell development is not known. Our study demonstrates that the essential transcription activator of the molecular clock, Bmal1, exerts direct temporal control of the TGF-b pathway, a key inhibitory signal of brown fat formation (Fournier et al, 2012;Koncarevic et al, 2012;Yadav et al, 2011). Together with reciprocally altered BMP activity, these developmental signaling mechanisms driven by Bmal1 modulate brown adipogenesis and consequently affect adaptive thermogenesis in vivo.…”
Section: Discussionmentioning
confidence: 77%
“…As TGF-b and BMPs are key negative and positive signals controlling brown fat formation, respectively (Fournier et al, 2012;Koncarevic et al, 2012;Tseng et al, 2008;Yadav et al, 2011), we postulated that Bmal1 might alter the activities of these pathways to affect brown adipocyte differentiation. We thus determined TGF-b signaling activities in Bmal1 loss-and gain-of-function cells using the TGF-bresponsive luciferase reporters 36TP-Luc (Wrana et al, 1992) and SBE4-Luc (Zhou et al, 1998).…”
Section: Bmal1 Inhibits Brown Adipocyte Terminal Differentiation and mentioning
confidence: 99%
“…RAP-435 is a recombinant fusion protein derived from an optimised human activin receptor IIB extracellular domain (ACTRIIB) fused to a human IgG1 Fc domain [31]. RAP-435 can block ACTRIIB signalling and shows higher affinity for activin B compared with other TGF-β superfamily ligands [31].…”
Section: Resultsmentioning
confidence: 99%
“…RAP-435 can block ACTRIIB signalling and shows higher affinity for activin B compared with other TGF-β superfamily ligands [31]. In order to assess whether endogenous activin B can exert homeostatic functions in the regulation of glucose and insulin levels in naive animals, we treated adult wild-type mice with RAP-435 for 4 weeks and examined fasting insulin and glucose levels, as well as glucose tolerance.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, MSTN inhibition enhances mitochondrial function and uncoupled respiration, thereby increasing energy expenditure (Fournier et al, 2012). Another study found that suppressed ACTRIIB can treat diet-induced obesity and induce a brown fat-like thermogenic gene program in white adipose tissue (Koncarevic et al, 2012). The results of these studies can have major implications for sports that require a low percentage of adipose tissue and for the treatment of obesity.…”
Section: Gene Doping and Physical Perfor-mancementioning
confidence: 99%